Infants and toddlers : evelopment and program planning - Deiner, Penny Low. (Fort Worth, TX : Harcourt Brace College, 1997)
This book is divided into two parts: Developmental processes; From theory to practice: Planning programs and activities for Infants, Toddlers, and Twos.
Keywords: Children; Infants; Children -- Language; Child development; Infants -- Development; Infants -- Growth; Infants -- Care; Exercise for children; Early childhood education -- United States -- Curricula